2014
DOI: 10.1155/2014/923561
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Helminths in Slaughtered Cattle in Ibadan, South-Western Nigeria

Abstract: As part of an ongoing project to investigate the epidemiology of gastrointestinal helminths of cattle in Nigeria, we carried out a systematic random sampling of cattle slaughtered in a major abattoir in Ibadan, south-western Nigeria. Using sedimentation and floatation methods, we analyzed fecal samples from 397 animals between March and May 2013. Overall, 163 (41.6%) of the animals had at least one gastrointestinal helminth egg, comprising a total of eight helminths from different genera (i.e., four nematodes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 16 publications
5
23
3
Order By: Relevance
“…Those GIT parasite mostly caused by nematode, cestode, trematode and protozoa in domestic animals and affects fertility, work capacity, involuntary culling, reduction in food intake, weight & milk production and higher mortality rate. 18,19 The findings of present study show that from 400 of the cattle screened, 46.8% (187) of animals had at least one GIT parasite infection which was similar with the result study of Adedipe et al 20 on the prevalence gastrointestinal helminths in slaughtered cattle in Ibadan, South-Western Nigeria which was 41.6% and of Lemy and Egwunyenga 21 on the prevalence of parasitic helminthes at various abattoirs in Abraka, Delta State, Nigeria which was 50.4%. However, it was less than that of other study result of Waruiru et al 22 researcher in different parts of the other country.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Those GIT parasite mostly caused by nematode, cestode, trematode and protozoa in domestic animals and affects fertility, work capacity, involuntary culling, reduction in food intake, weight & milk production and higher mortality rate. 18,19 The findings of present study show that from 400 of the cattle screened, 46.8% (187) of animals had at least one GIT parasite infection which was similar with the result study of Adedipe et al 20 on the prevalence gastrointestinal helminths in slaughtered cattle in Ibadan, South-Western Nigeria which was 41.6% and of Lemy and Egwunyenga 21 on the prevalence of parasitic helminthes at various abattoirs in Abraka, Delta State, Nigeria which was 50.4%. However, it was less than that of other study result of Waruiru et al 22 researcher in different parts of the other country.…”
Section: Discussionsupporting
confidence: 90%
“…However, it was less than that of other study result of Waruiru et al 22 researcher in different parts of the other country. 12,[20][21][22][23][24][25][26] Furthermore, the study showed that paramphistomum eggs were the most prevalent among the parasite which has prevalence of 38.5%. This prevalence was greater than the reported study that was conducted at Wukari Local Government abattoir, in Taraba State, North-Eastern Nigeria which was 23.70% 28 ; furthermore, it was disagree with reported result of Ayalew et al 29 who reported paramphistomum prevalence which was greater than the study which was 51.82% in Gondar Elfora Abattoir.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of 100% of GI parasite infection obtained in this study was higher than those by [19] and [20] who reported a prevalence of 47.4% and 41.6% in South-South and South-West Nigeria respectively. It was also higher than 50.8% and 62.1% earlier reported in South-Eastern and South-South Nigeria by [4] and [21] respectively.…”
Section: Discussioncontrasting
confidence: 83%
“…In this study, different breeds of cattle and some of their crosses were encountered at the study location. Earlier study by other workers [14] lends credence to the fact that different breeds of cattle and their crosses are brought from the northern parts of the country (Nigeria) into the abattoir where the study was undertaken. The implication of this is that frequent occurrence of crosses of different breeds of cattle is widespread in Nigeria.…”
Section: Discussionmentioning
confidence: 88%